Perbandingan Kinerja Non-Orthogonal dan Orthogonal Amplify and Forward pada Two-Way Cooperative WLAN - Kurnia Rizki; Nasaruddin; Ramzi Adriman (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Nowadays, the advancement of Wireless Local Area Network (WLAN) technology has developed very rapidly because it is very practical and has effective mobility level. In practice, there is a major problem in wireless communications systems, which is fading. Fading can cause information signal power decreasing. Fading can be overcome using a cooperative communication system, which is a method that utilizes antenna from other users (relays), using principle of diversity, hence the performance of wireless communication system is improved. A relay has several protocols on cooperative communication system, such as Amplify and Forward (AF), Decode and Forward (DF), and Compress and Forward (CF). The AF protocol is divided into two types: Non-Orthogonal Amplify and Forward (NAF) and Orthogonal Amplify and Forward (OAF). In this paper, the performance comparison of two-way NAF and OAF in terms of outage probability, throughput, and spectral efficiency is investigated. The method used is computer simulation with system modeling and performance analysis. The simulation results show that OAF protocol can minimize outage probability and increase throughput and spectral efficiency, compared to NAF protocol on two-way WLAN cooperative network.